EVALUATION OF LATVIAN FLAX VARIETIES BY SEED YIELD AND QUALITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Flax cultures give dual-purpose production – flax fibre and seeds. Flax varieties adapted to local climate conditions have breeded but up to now the profound research of its quality was not carried out. In our investigation we analysed flax varieties of Latvia selection for seed yield and quality in comparison with standard varieties ‘Vega 2’ and ‘Lirina’. In Latgale Agricultural Scientific Centre 10 Latvian flax varieties are cultivated and seed yield, 1000-seed weight, seed oil content (extracted by hot pressing method) and fatty acid content in flax seed oil (detected with gas chromatography method) have evaluated. Seed yields of fibre flax Latvian varieties are significantly higher in comparison with standard variety ‘Vega’. All analysed seed samples have high oil content (27- 47%) and there is high percentage of polyunsaturated fatty acids in oil (linoleic acid 10,6-16,9%, linolenic acid 54,7-62,1%). There is little difference in 1000-seed weight, content of oil in seeds, percentage of linoleic, linolenic, oleic, palmitic and stearic acid in oil between fibre flax and oil seed flax varieties. The difference between the varieties is more influential. Flaxes seeds from Latvian varieties are in high quality and can be used for food, medical and technical purposes.